2013
DOI: 10.1136/oemed-2013-101717.377
|View full text |Cite
|
Sign up to set email alerts
|

377 Occupation and risk of lymphoid and myeloid leukemia in the European Prospective Investigation into Cancer and Nutrition (EPIC)

Abstract: Objectives Established risk factors of leukemia do not explain the majority of leukemia cases. Previous studies have suggested the importance of occupation and related exposures in leukemogenesis. We evaluated possible associations between job title and selected hazardous agents and leukemia in the European Prospective Investigation into Cancer and Nutrition. Methods The mean follow-up time for 241,465 subjects was 11.20 years (SD: 2.42 years). During the follow-up period, 477 incident cases of myeloid and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Since the cancer is one of occupational-related disease, as (Park et al, 2014) concluded it in their study (A case of chronic myeloid leukemia in a diagnostic radiographer), also (Löffler et al, 2001) in the study (Reduced risk for chronic myelogenous leukemia in individuals with the cytochrome) concluded that; Most cancers can be attributed to the environmental factors that act in conjunction with genetic readiness. As a result of the conclusions of these studies the development of chronic myeloid leukemia may correlate with exposure to many types of environmental agents according to the nature of the type of patient's occupation, for example: (Saberi Hosnijeh et al, 2013) concluded that exposure to radiation, inhalation of benzene, smoke of cars and generators are one of chronic myeloid leukemia risk factors.…”
Section: Figure (mentioning
confidence: 99%
“…Since the cancer is one of occupational-related disease, as (Park et al, 2014) concluded it in their study (A case of chronic myeloid leukemia in a diagnostic radiographer), also (Löffler et al, 2001) in the study (Reduced risk for chronic myelogenous leukemia in individuals with the cytochrome) concluded that; Most cancers can be attributed to the environmental factors that act in conjunction with genetic readiness. As a result of the conclusions of these studies the development of chronic myeloid leukemia may correlate with exposure to many types of environmental agents according to the nature of the type of patient's occupation, for example: (Saberi Hosnijeh et al, 2013) concluded that exposure to radiation, inhalation of benzene, smoke of cars and generators are one of chronic myeloid leukemia risk factors.…”
Section: Figure (mentioning
confidence: 99%